El rol de las redes sociales y el empoderamiento de las mujeres en medicina - Espinoza-Portilla, Elizabeth (2020)
Today, the number of doctors and health professionals who use social networks as main venues for communication is increasing. Social networks offer new ways to connect and can facilitate almost instantaneous communication without geographical boundaries and can support students, doctors and health professionals. Social networks can allow women in the health field to obtain support that they would not otherwise have. This article describes the role of social networks in contributing to the empowerment of women in medicine and discusses the opportunities to use social networks as a tool for: access to mentoring and experienced counselors as role models; peer support and interaction; and access to information and continuing education.